2022
DOI: 10.1109/access.2022.3147980
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid LSTM-ResNet Deep Neural Network for Noise Reduction and Classification of V-Band Receiver Signals

Abstract: Noise reduction is one of the most important process used for signal processing in communication systems. The signal-to-noise ratio (SNR) is a key parameter for minimizing the bit error rate (BER). The inherent noise in millimeter-wave systems is mainly a combination of white and phase noise. Increasing the SNR can lead to reliability and performance improvements in wireless data transfer systems. To address this issue, we propose to use a recurrent neural network (RNN) with a long shortterm memory (LSTM) auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Figure 1C depicts the unit structure of the LSTM neural network, which regulates data through a forget gate, input gate, and output gate [34]. The forget gate f t σ(W f [J t−1 , x t ] + b f ) governs the information preserved from the preceding neuron.…”
Section: Mf-lstm Algorithmmentioning
confidence: 99%
“…Figure 1C depicts the unit structure of the LSTM neural network, which regulates data through a forget gate, input gate, and output gate [34]. The forget gate f t σ(W f [J t−1 , x t ] + b f ) governs the information preserved from the preceding neuron.…”
Section: Mf-lstm Algorithmmentioning
confidence: 99%
“…In addition, in order to further improve the recognition accuracy of communication radiation sources, part of the research works [ 6 ], Refs. [ 20 , 21 ] combined the manually extracted expert features with deep learning to obtain fusion features. However, the essence of the above works is still only to extract inter-class separable features.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, data-driven strategy based on massive data and deep learning has become popular. A lot of studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] have confirmed that deep learning has a strong feature extraction ability, which makes it superior to traditional methods in many recognition tasks. However, these works are mainly based on improved or new proposed network models.…”
Section: Introductionmentioning
confidence: 99%
“…This method is based on the combination of LSTM optimization model and regularized K-SVD. The LSTM sequence prediction network demonstrates excellent proficiency in handling time series data, capturing both longterm and short-term dependencies [23] [24]. On the other hand, the regularization K-SVD algorithm excels in handling sparse representations of signals, capable of filtering out noise and extracting key signal features [25] [26].…”
Section: Introductionmentioning
confidence: 99%